Presence of Gingival Recession or Noncarious Cervical Lesions on Teeth under Occlusal Trauma: A Systematic Review - Senos Tróia, Pedro Maria Bastião Peliz; Spuldaro, Tobias Rauber; da Fonseca, Patrícia Alexandra Barroso; Fernandes, Gustavo Vicentis de Oliveira (European Journal of General Dentistry, 2021)
The goal of this research was to carry out a systematic review to verify the possible influence of occlusal factors on the occurrence of gingival recession and noncarious cervical lesions. To answer the specific research question—whether gingival recession or noncarious cervical lesions on teeth are present under occlusal trauma—a bibliographic search was conducted at MEDLINE/PubMed, Web of Science, and Gray Literature databases focusing on articles published, following strict inclusion criteria based on randomized clinical trials, controlled clinical studies, and case series, with restricted language (English) and publication date between March 2010 and March 2020, considering patients with occlusal trauma and gingival recession/noncarious cervical injuries. Questionnaires, animal or laboratory studies, case reports, and interviews were excluded. First, the title and/or abstract of the articles obtained were analyzed and, finally, a full-text reading was performed. Given the amount and diversity of the final studies, a qualitative analysis was made. Based on the established criteria, it was possible to obtain an initial 757 articles. After screening, five articles were included, and then qualitative analysis was performed. The results described in the articles were different, given the heterogeneity of the articles subjected to analysis. A few studies were published in the past 10 years, suggesting that the traumatic occlusion seems to be associated with the occurrence of the noncarious cervical lesion while it is not possible to arrive at a conclusion with regard to the association of gingival recession and occlusal trauma.Key MessageEven though many professionals have categorically affirmed that there is a relation between trauma occlusal and gingival recession/noncarious cervical lesion, this systematic review found the absence of strong literature to really prove it. Once defined, it allows the therapeutic focus to centre on the causal or contributing factors and preventing or reducing future recurrence.
Keywords: dental occlusion; gingival recessions; noncarious cervical lesions; occlusal trauma; systematic review